The Communication Barriers in a Ukrainian Family: Adultery and Socio-Psychological Aspects - Prib, Hlib A.; Bondar, Svitlana S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
A common cause of disruption of family communication is adultery, which creates a traumatic situation and even leads to family destruction. The purpose of the article is to investigate sexual and psychosocial disorders in family communication under adultery—research methods. The study used validity methods «Eysenck Inventory of Attitudes to Sex» and «Diagnostics of the inferiority complex». Statistical methods. For the non-parametric data correlation variables, the Spearman coefficient was used, Kendall’s, Pearson’s. Results: The present study found the destructive effect of the psychological characteristics of sexuality on family functioning in CGA. The connection between disappointment with existing sexual relations and desire for sexual satisfaction was established (p <0.05). Conflicts between beliefs and internal impulses were detected (p <0.05). It was found that treating a partner as a sexual object without finding sensual pleasure correlated with intolerance to a verbal description of bed scenes (p <0.05). Sexual shyness is a characteristic of couples with sexual inactivity and aversion to sexual manifestations (p <0.05). In turn, the difficulty of acquiring sexual excitement correlated with a fascination with only physical sex without its spiritual component (p <0.05). Conclusion: Features of the psychological response of men and women in CGA and CG in the genesis and development of impaired family life are connected to the following: a great number of complexes and constant struggle with personal weaknesses, drawbacks, mistakes; fear of analyzing oneself and one’s own actions by "hiding" and "postponing" the resolution; inflated self-esteem, self-deception, living in the so-called "imaginary world", low communication (p <0.05).